2019
DOI: 10.18203/2394-6040.ijcmph20195059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and the nutritional status of oral cancer treated patients as compared with the control group in Varanasi district: a cross sectional study

Abstract: They are also associated with economic, social and psychological impacts that impinge on oral function, appearance, and social interactions, leading to the disruption of the daily routines. 3Quality of life is multidimensional and it is based mainly on the individual functional health status, level of pain, self-attribution, self-perception and quality of interaction ABSTRACT Background: The modern day oral oncotherapy is now concerned on the oral quality of life after treatment of the patient. There is need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A group from Chennai reported that oral cancer is most prevalent at the base of the tongue and the base of the mouth that enhances the metastasis [ 12 ]. Another group has reported that buccal mucosa, alveolus, and the base of the mouth are the most prevalent sites for the occurrence of oral cancer [ 13 ]. It is also reported that the nutritional diet is important for oral cancer patients to maintain the oral health-associated quality of life.…”
Section: Status Of Oral Cancer In Indiamentioning
confidence: 99%
“…A group from Chennai reported that oral cancer is most prevalent at the base of the tongue and the base of the mouth that enhances the metastasis [ 12 ]. Another group has reported that buccal mucosa, alveolus, and the base of the mouth are the most prevalent sites for the occurrence of oral cancer [ 13 ]. It is also reported that the nutritional diet is important for oral cancer patients to maintain the oral health-associated quality of life.…”
Section: Status Of Oral Cancer In Indiamentioning
confidence: 99%
“…The lip, tongue, gums, palate, and other parts of the oral mucosa are the most pervasive sites of OC, as classified by the International Classification of Diseases (ICD) [4]. A lot of people who have oral cancer have a lot of different things going on in their mouths, including smoking, drinking too much alcohol, not brushing their teeth, and having long-term viral infections, such as the human papillomavirus (HPV) [5][6][7][8][9]. Tobacco use (in every form) is an important cause of cancer, particularly in underdeveloped nations.…”
Section: Introductionmentioning
confidence: 99%